Preferred Teaching Strategies for Students in an Associate of Science Nursing Program. - Young, Diane; Seibenhener, Sherry (Teaching & Learning in Nursing, 2018)
The constituents of the nursing classroom have evolved over the years from the traditional high school graduate to a multigenerational student population. Diversity in student demographics brings new challenges to educators. Implementation of innovative teaching strategies has now become a driving force in nursing education to better meet the needs of a multigenerational classroom.